Experimental and Computational Fluid Dynamics Study of the Flow Field of a Model Pump Turbine - Deng, Yuxuan; Xu, Jing; Li, Yanna; Zhang, Yanli; Kuang, Chunyan (Frontiers in Energy Research, 2022)
The pumped storage unit has a hump area and S characteristics during operation. The operating conditions of the unit are complex, and it is necessary to switch between working conditions. The unit frequently crosses the hump area and the S characteristic area, thus hindering the unit to connect to the grid. Severe vibration affects the safe and stable operation of a power station. With the joint efforts of the industry, the impact of the hump and S-shaped problems on project commissioning has been fundamentally resolved, but the mechanism of inducing hump and S-shaped problems has not yet been well established. Therefore, in this study, the particle image velocity measurement method based on a full-characteristic test was adopted. According to the operating characteristics of the unit, 32 operating points with four guide-vane opening degrees were selected to test the flow pattern in the vaneless space. After subtracting the average flow velocity, the vortex image of the leafless area was obtained, which provided a reference for the design of the runner of the water pump turbine.